Olympia 2016: Fakta og kontrafakta - Damkjær, Søren (Forum for Idræt, 2003)
En forudsigelse af idrætssamfundet og den olympiske bevægelse i år 2016. Olympia 2016: Facts and counterfacts In Idrætshistorisk Årbog (Yearbook of Sporting History) no. 4 in 1988, which also took the Olympic Games as its theme, Søren Damkjær wrote a science fiction article in which from the postulated vantage point of 2020 he took a retrospective look at the 2000 Games, which he had transferred to Manila. For the current number (2003) about the Olympic movement, the editor asked Søren to assess the validity of the 1988 article. The working title is “Was Søren right?”. This is what Søren Damkjær considers in this article, which takes as its starting point a pre-Olympic conference in St. Petersburg in 2016. The main conclusion is that by and large he was wrong!